2015
DOI: 10.1016/j.combustflame.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of combustion instability limit cycle oscillations by combining flame describing function simulations with a thermoacoustic network model

Abstract: a b s t r a c t Accurate prediction of limit cycle oscillations resulting from combustion instability has been a long-standing challenge. The present work uses a coupled approach to predict the limit cycle characteristics of a combustor, developed at Cambridge University, for which experimental data are available (Balachandran, Ph.D. thesis, 2005). The combustor flame is bluff-body stabilised, turbulent and partially-premixed. The coupled approach combines Large Eddy Simulation (LES) in order to characterise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(86 citation statements)
references
References 95 publications
(173 reference statements)
0
86
0
Order By: Relevance
“…Based on the PaSR model, the filtered chemical reaction rate of the i -th species, , can be scaled by κ and modelled as [23, 40]: where denotes the mean concentration of species i exiting the mesh cell, and is the initial mean concentration of species i inside the same cell. Δ t is the computational time step, and denotes the density-weighted (Favre) filtering, defined as for an arbitrary variable ψ .…”
Section: Large Eddy Simulation Of a Turbulent Reacting Flow-fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the PaSR model, the filtered chemical reaction rate of the i -th species, , can be scaled by κ and modelled as [23, 40]: where denotes the mean concentration of species i exiting the mesh cell, and is the initial mean concentration of species i inside the same cell. Δ t is the computational time step, and denotes the density-weighted (Favre) filtering, defined as for an arbitrary variable ψ .…”
Section: Large Eddy Simulation Of a Turbulent Reacting Flow-fieldmentioning
confidence: 99%
“…Previous large eddy simulations (LES) [2123] and experiments [24] of combustor reacting flow-fields have shown that the main large-scale flow features, such as flow separation and recirculation zones, are the same whether the flame is fully-premixed [22], partially-premixed [23], or non-premixed [21, 24]. The mean and fluctuating velocity fields are both qualitatively and quantitatively very similar in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that a large number of calculations is required to accurately estimate the FDIDF. This makes it currently non-affordable f or, say, compressible LES studies, in which many CPU hours are already required to calculate the FDF only [57] .…”
Section: Discussion On Cost and Practical Implementationmentioning
confidence: 99%
“…In order to study the thermoacoustic modes, we use a low order thermoacoustic network modelling tool -in this case the open source OSCILOS [15,25] which has been validated against experiments [26]. As shown in Fig.…”
Section: The Effect On Thermoacoustic Modesmentioning
confidence: 99%